A review of the nutritional guidance for athletes to prevent eating disorders - Hilling, J. J.; Robertson, C. (European Eating Disorders Review, 2023)
Since the 1980s eating disorders (ED) have gained increasing prevalence, with athletes proving to be at a higher risk compared to non-athletes. Eating disorders can significantly impact the health and performance of an athlete, however, certain guidelines are in place for prevention, treatment and management. NICE and UK Sport were two guidelines that were identified as being referenced within the UK. This paper aimed to evaluate their utility and establish whether modifications are required to prevent ED within athletic populations. A checklist was created based on peer-reviewed recommendations and used in conjunction with conceptualised case studies based on information sourced from proposed key informant interviews. Whilst both guidelines are extensive in the identification of symptoms associated with ED, they lack recognised recommended screening methods. Furthermore, although both contain some form of validated treatment, NICE recommends cognitive behavioural therapy despite acknowledging the lack of evidence supporting its beneficial application. In contrast to recommendations regarding physical therapy, NICE also states to avoid certain treatments, such as yoga, despite beneficial evidence of its treatment/rehabilitation for ED. When applied to case studies, both guidelines demonstrated the need for refinement and improvement in recommendations relating to weight loss and screening methods. To form an accurate critique of the guidelines, an assessment of their applicability and suitability in the prevention, treatment and management of ED in a practical sporting environment involving consenting participants is required.